East Asia and global imbalances: Saving, investment, and financial development - Hiro Ito; Menzie Chinn (University of California, Santa Cruz Institute for International Economics (SCIIE), 2007)
We investigate the role of budget balances, financial development and openness, in the evolution of global imbalances. Financial development or the lack thereof has received considerable attention as a possible contributing factor to the development of persistent and expanding current account imbalances. Several observers have argued that the depth and sophistication of US capital markets have caused capital to flow from relatively underdeveloped East Asian financial markets. In this paper, we extend our previous work by examining the effect of different types and aspects of financial development. Our cross-country analysis, encompassing a sample of 19 industrialized countries and 70 developing countries for the period of 1986 through 2005, yields a number of new results. First, we confirm a role for budget balances in industrial countries when bond markets are incorporated. Second, empirically both credit to the private sector and stock market capitalization appear to be equally important determinants of current account behavior. Third, while increases in the size of financial markets induce a decline in the current account balance in industrial countries, the reverse is more often the case for developing countries, especially when other measures of financial development are included. However, because of nonlinearities incorporated into the specifications, this characterization is conditional upon other factors. Fourth, a greater degree of financial openness is typically associated with a smaller current account balance in developing countries.
Keywords: F32; F41; 330; current account; net foreign assets; saving glut; investment drought; panel regressions; capital controls; institutional development; Zahlungsbilanzgleichgewicht; Internationaler Finanzmarkt; Sparen; Öffentliche Schulden; Offene Volkswirtschaft; Industriestaaten; Entwicklungsländer